The innovator's DNA : mastering the five skills of disruptive innovators - Dyer, Jeff (Harvard Business, 2011)
A new classic, cited by leaders and media around the globe as a highly recommended read for anyone interested in innovation. In "The Innovator s DNA," authors Jeffrey Dyer, Hal Gregersen, and bestselling author Clayton Christensen ("The Innovator s Dilemma," "The Innovator s Solution," "How Will You Measure Your Life?") build on what we know about disruptive innovation to show how individuals can develop the skills necessary to move progressively from idea to impact. By identifying behaviors of the world s best innovatorsfrom leaders at Amazon and Apple to those at Google, Skype, and Virgin Groupthe authors outline five discovery skills that distinguish innovative entrepreneurs and executives from ordinary managers: Associating, Questioning, Observing, Networking, and Experimenting. Once you master these competencies (the authors provide a self-assessment for rating your own innovator s DNA), the authors explain how to generate ideas, collaborate to implement them, and build innovation skills throughout the organization to result in a competitive edge. This innovation advantage will translate into a premium in your company s stock pricean innovation premiumwhich is possible only by building the code for innovation right into your organization s people, processes, and guiding philosophies. Practical and provocative, "The Innovator s DNA" is an essential resource for individuals and teams who want to strengthen their innovative prowess.